Aprovechamiento didáctico de un comentario léxico - Fabián González Bachiller (Universidad de La Rioja, 2013)
From a brief literary fragment, a lexico-semantic commentary is proposed, in order for the university student to prove the relation between the linguistic forms and the social and natural environment. For that purpose, the study of characteristic regional and rural words in the text is emphasized. On the other hand, the use of dictionaries as indispensable tools for the mastering of vocabulary is highlighted.